A new variety of spring barley ‘Gris’ - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; T. I. Firsova; A. S. Popov; M. M. Kopus (Зерновое хозяйство России, 2018)
The increase of grain production is a key purpose of agricultural development in Russia. Spring barley largely determines the amount of gross grain yields in the regions of RF, including North Caucasus. Being principal forage crop, its grain is raw material for brewery, food and other types of production. Its specific weight in the production of forage grain was 80% for the last years, its share in the amount of sowing areas was more than 30%. On the present stage of agricultural development it is necessary to develop highly productive varieties with good agro ecologic stability to increase gross yield of spring barley and to supply husbandry with valuable forage grain. The early maturity is one of the main mechanisms protecting plants from summer droughts. The article gives economic-biological characteristics of a new early maturing drought tolerant variety of spring barley ‘Gris’, introduced into the State List of Breeding Achievements in North Caucasus in 2016. The new variety possesses high plasticity and productivity. The variety exceeds the main zoned varieties in resistance to lodging and in tolerance to regional diseases under artificial and natural infection. The introduction of the spring barley variety ‘Gris’ will play a definite part in the improvement of barley productivity, stability of the crop and complete supply with valuable forage grain.